El último viaje de Orfeo: Los diarios de Emilio Renzi - Teresa Orecchia Havas (Cuadernos LIRICO)
This article analyzes the “will of literature” visible in Los diarios de Emilio Renzi. On that purpose, it discusses the external and internal evidence which reveal the literary nature of the Diarios, beginning by the chronology of the editing and the previous partial publications of texts; this leads to some adjustements of the notion of  “posthumous” (work). On the field of internal evidence, the essay comments Piglia’s practices of rewriting and focuses on the structure of the three volumes as well as on the transfer from the author’s voice to Emilio Renzi’s one. This last device is associated here with some of Piglia’s themes and with his fictional images of literary voices being in a frontier between life and death. Imaginary, phantasmatic and biographical elements coincide then in this main strategy to make the diary a litterary masterpiece. The Diarios are the (last) great Piglia’s travel to literary creation; it looks again towards the origins and fights against the idea of definite ends. The Annexe section examines some data recovered in Piglia’s files of Princeton University.